Characterization of light diesel fraction obtained from upgraded heavy oil - Yakup Kar; Dilek Şenel Göksu; Yusuf Yalman (Egyptian Journal of Petroleum)
In this study, the role of a low-cost catalyst (activated molasses soil) over the hydrocarbon distribution of the light diesel (or distillate) fraction of the pre-upgraded heavy crude oil (Bati Raman) was examined in detail. The low-cost catalyst showed a strong impact on the hydrocarbon distribution of the light diesel fuel fraction. The physicochemical characteristics such as hydrocarbon group distribution, density and kinematic viscosity of the light diesel fuels obtained from the upgraded heavy oil indicated a proper consistency with those having the commercial diesel fuels. As a result, it was revealed that the low-cost material could be successively used in the heavy oil upgrading to obtain the light diesel fuels. Keywords: Light diesel fuel, Catalytic upgrading, Molasses soil, Hydrocarbon distribution, Characterization